ANALISIS PERFORMA PERSONEL PADA SATUAN RESERSE KRIMINAL POLRESTA BANDAR LAMPUNG DAN POLSEK JAJARAN DI BANDAR LAMPUNG - Widha, Bhira (Jurnal Manajemen Magister Darmajaya, 2017)
Indonesian National Police is an instrument of the state that play a role in maintaining internal security and law enforcement in the community. In this position so it is natural that the police performance evaluation is desirable in order to create public trust and maintaining internal security.The study aimed to determined the relationship between discipline, motivation and job performance with Performance Personnel At the Police Criminal Investigation Unit and the Police Board of Bandar Lampung. The method used in this study is qualitative, data collection instruments used by researchers is observation, interview and documentation. The results shows that discipline, motivation and job performance are variables to support the optimal performance of personnel of the Police Criminal Investigation Unit Bandar LampungÂ Keywords : Personnel Performance, Discipline, Motivation, Work Performance